Door-to-Door Health Education to Increase Community Knowledge in Preventing Covid-19 - Prayudhy Yushananta; Mei Ahyanti; Bambang Murwanto; Enro Sujito; Yenni Rosita (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Coronavirus disease (COVID-19) caused by SARS-COV-2 has a very high transmission rate and can potentially cause deaths. This disease is a great public health concern globally and considered as humanitarian disaster. Person-to-person transmission of COVID-19 occurs through close contact and droplets. Therefore, the preventions should be done through wearing masks, hand washing with soap, and social distancing. The spreading of misinformation causes a low level of public awareness. It will increase the risk of spreading the disease. This community service aims to increase public knowledge about the prevention and expansion of the COVID-19 disease. One hundred target households were visited and educated during the service. We have also distributed 250 masks and 500 leaflets and put up banners in open places containing what and how to prevent COVID-19. Installation a portable hand washing sink with soap was also carried out to reduce transmission risks. Dissemination of valid information must be carried out to change people’s behaviors. The involvement of all elements of society are needed to create a new normal era of life.